Tumoral Expression of CD44 and HIF1α Predict Stage I Oral Cavity Squamous Cell Carcinoma Outcome - Dunkel J; Vaittinen S; Koivunen P; Laranne J; Mäkinen MJ; Tommola S; Irjala H (My University, 2022)
Objectives/Hypothesis
No biomarkers are used to estimate the prognosis in oral cavity squamous cell carcinoma (OSCC). In our previously published work, we have reported the prognostic value of CD44 and hypoxia inducible factor (HIF)−1α in patients with stage I disease.
Study Design
In this study, we tested our previous observations in a larger cohort. We also studied the predictive value of common lymphatic endothelial and vascular endothelial receptor (CLEVER)−1 in this material.
Methods
CD44, HIF1α, and CLEVER-1 were immunohistochemically analyzed in paraffin-embedded tissue material of stage I OSCC patients treated at three Finnish university hospitals. Microscopy results were correlated with OSCC outcome.
Results
As in our pilot study, the CD44lowHIF1αhigh signature was associated with poorer disease-free survival. Clear correlations between CLEVER-1 expression and clinical outcome were not evident.
Conclusion
Our results suggest that immunohistochemistry of CD44 and HIF1α may be useful in identification of patients with poor prognoses. These parameters could be used to select the optimal treatment modalities for stage I OSCC patients.